Composição e estrutura de uma taxocenose de serpentes em remanescente de Mata Atlântica de uma região metropolitana do Nordeste do Brasil - Cardoso, Gabrielle de Souza (2022)
Assemblage composition and structure are determined by interactions between ecological and biogeographical processes. Snakes ecology and diversity patterns are reflected in morphological attributes and natural history, covering information about diet, substrate usage and daily activity. In this study were evaluated composition and natural history, morphological phylogenetic struture and urbanization effects on snakes assemblage from São Cristóvão – SE, on an Atlantic Forest remnant surrounded by urban matrix. On assemblage were registrated 27 snake species which most has environmental plasticity and wide geographical distribution. Added to low availability of vegetation strata, these factors influence the predominance of species that exploit terrestrial substrates and diet generalists. Influence of urban matrix were not observed on biogeographic similarity and phylogenetic diversity indexes, which are possibly determined by spacial clustering in the biome. Composition and phylogenetic diversity of São Cristóvão assemblage are similar to other areas in Atlantic Forest, including protected areas for conservation, and biogeographic similarity is greater with those ones of Northern portion of the biome. Morphological structure of São Cristóvão is influenced by both phylogeny and ecology, being possible visualize groupings regarding substrate usage, similar to patterns previously observed in Caatinga and Cerrado. These results show the importance of incorporating historical processes in studies of snakes assemblages and considering urban areas as study object, which makes possible understand biodiversity and how assemblages are structured in areas with environmental disturbances.